Mesangial angiogenesis and interstitial eosinophilic infiltration in diabetic nephropathy are associated with elevated CD248 expression - Xiangmeng Li; Jiao Zhang; Ying Wang; Tianyu Yu; Shimin Jiang; Yan Gao; Haisong Zhang; Wenge Li (Renal Failure)
Objectives To investigate the factors associated with angiogenesis within the glomerular mesangial area and interstitial eosinophilic infiltration in diabetic nephropathy (DN).Methods The NCBI database identified differentially expressed genes (DEGs) in DN patients linked to angiogenesis and inflammation. Bioinformatics analyzed these genes and mechanisms. In vivo (DN patients and db/db mice) and in vitro experiments explored glomerular mesangial angiogenesis and interstitial eosinophilic infiltration mechanisms.Results Twenty-five independent DEGs associated with DN were identified, and CD248 was associated with vessel formation and inflammatory cells. Biological analysis suggested CD248 mainly promoted vessel formation and eosinophilic infiltration via VEGFC and CCL-5, respectively. In DN patients, neovascularization with CD31-positive endothelial cells was observed in the mesangial regions, which was accompanied by increased expression of CD248 and VEGFC. Eosinophilic infiltration was observed in the renal interstitium, and the degree of eosinophilic infiltration was positively correlated with the intensity of CD248 expression. Serial section analysis revealed that areas with increased eosinophilic infiltration exhibited stronger infiltration of CD3-positive cells and elevated CCL-5 expression. Similar findings were discovered in the db/db mice, with WB results demonstrating higher expression levels of CD248, CCL-5, and VEGFC in the renal tissues of db/db mice compared with m/m mice. In vitro, CD248 expression is low in mesangial cells, but increased under high-glucose/LPS. CD248 siRNA reduced high-glucose/LPS-induced VEGFC/CCL-5.Conclusion In DN, CD248 may contribute to mesangial angiogenesis and renal interstitial eosinophilic infiltration; these pathological processes may be associated with the elevated expressions of VEGFC and CCL-5, respectively.